Pengaruh pendidikan gizi pada murid sekolah dasar terhadap peningkatan pengetahuan, sikap dan perilaku ibu keluarga mandiri sadar gizi di Kabupaten Indragiri Hilir - Zukarnaini Zulkarnaini; Toto Castro; Untung Widodo (Jurnal Gizi Klinik Indonesia, 2006)
Background: KADARZI could be realized by optimizing the role of family, namely by increasing nutrition knowledge, changing attitude and behavior and developing independent family. The poor knowledge, attitude and behavior of society, especially house wives, to-ward nutrition and health are important factors which influence the realization of KADARZI programme. The evaluation of KADARZI programme in 2002 in Indragiri Hilir resulted 22.41% from the target 80%. One way to increase society’s knowledge, attitude and behavior toward nutrition is by giving nutrition education during early life.Objective: The study was purposed to investigate the influence of nutrition education among elementary school students to KADARZI house wives knowledge, attitude and behavior.Method: This was quasi experimental with non-randomized control group pretest-posttest study. Subjects were elementary students in the fourth, fifth, and sixth class along with their mothers. The place was in Indragiri Hilir district. Subjects were gathered by purposive. The quantity of subjects were determined with sample formulation, knowledge, attitude and behavior data were gathered by interview and observation adjusted in questionnaire list. Characteristic was analyzed with chi square, statistic test with t-test, with significance level of p=0.05.Result: The analysis of age, education, occupation, the number of household members and family income of both group were similar. Pretest analysis of knowledge, attitude and behavior among students and mothers in both groups were also similar in both groups before intervention. Posttest analysis of knowledge, attitude and behavior of treatment group were significantly increased (p<0.05). While in the control group showed insignificant differences (p>0.05). Analysis among mothers whose children got no intervention showed there were no significant differences (p>0.05). While mothers whose children got intervention showed insignificant differences in knowledge and attitude but behavior.Conclusion: Nutrition education about KADARZI on elementary student couldn’t increase mother’s knowledge and attitude but behavior.